Точечная коррекция рассеянного светового поля плоской решетки диэктрических резонансных наносфер - Гвинджилия, Г. Г. (ХНУРЭ, 2012)
Solutions of the problem on electromagnetic waves scattering on a flat grate of resonant spheres were considered